Exclusion and networks. The responsibilities of the actors in Hungarian spatial planning for the mitigation of exclusion - Jász, Krisztina (IGiPZ PAN, 2009)
Recently, it has been claimed that spatial inequalities in Hungary had by far not reduced, but signifi cantly increased since 1990. The inefficiency of Hungarian regional development in the reduction of spatial inequalities, in the past two decades has been caused by several different reasons. Functional deficiency of the local institutions of the regional development network is one of the most characteristic reasons, which led to this situation. Network members at the next planning turnover should be able to change the attitudes catalyse the changes necessary, being able to contribute to the realisation of a planning practice based on community development.
29 cm
Keywords: spatial inequality; network; community development